Outcomes of Minimally Invasive versus Open Surgery for Intermediate to High-grade Spondylolisthesis: A 10-Year Retrospective, Multicenter Experience. Issue 20 (15th October 2020) - Lak, Asad M.; Abunimer, Abdullah M.; Rahimi, Amina; Tafel, Ian; Chi, John; Lu, Yi; Groff, Michael; Zaidi, Hasan A.
Abstract : Study Design: Retrospective cohort study. Objective: The primary objective of our study was to evaluate the surgical outcomes and complications of minimally invasive surgery (MIS) versus open surgery in the management of intermediate to high grade spondylolisthesis, and secondarily to compare the outcomes following MIS in-situ fusion versus MIS reduction and open in-situ fusion versus open reduction subgroups. Summary of Background Data: High-grade spondylolisthesis is a relatively rare spine pathology with unknown prevalence. The optimal management and long-term prognosis of high-grade spondylolisthesis remain controversial. Methods: A multicenter, retrospective cohort study of adult patients who were surgically treated for grade II or higher lumbar or lumbosacral spondylolisthesis from January 2008 until February 2019, was conducted. Results: A total of 57 patients were included in this study. Forty cases were treated with open surgery and 17 with MIS. Specifically, seven patients underwent MIS in-situ fusion, 11 patients open in-situ fusion, an additional 10 patients underwent MIS reduction, and 29 had open reduction. Patients who underwent open surgery had significantly better pain relief at short-term follow-up with no statistically significant difference in the rate of complications (25% vs. 35.2%, P  = 0.44), as compared with MIS. The most common complications were related to instrumentation (17.7%), followed by neurological complications (14.5%), wound infection/dehiscence (6.5%), and post laminectomy syndrome (1.6%). The average follow-up time was 9.1 ± 6.2 months. In a subgroup comparison, the complication rate in the open in-situ fusion (36.3%) versus open reduction (20.6%) subgroup was non-significant ( P  = 0.42). However, complication rate in the MIS reduction group (55%) was significantly higher than MIS in-situ fusion ( P  = 0.03). Conclusion: MIS reduction is associated with a higher rate of complications in the management of grade II or higher lumbar or lumbosacral spondylolisthesis. The management of this complex pathology may be better addressed via traditional open surgery. Level of Evidence: 3